Community-based curriculum : instructional strategies for students with severe handicaps - Falvey, Mary A. (Baltimore, Maryland : P.H. Brookes Pub. Co., 1986)
This book is intended to provide parents, educators, therapist, counselors, and other concerned individuals with strategies for developing and implementing appropriate educational programs for individuals with severe handicaps.
Chapter One. Introduction -- Chapter Two. Assessment strategies -- Chapter Three. Instructional strategies -- Chapter Four. Community skills -- Chapter Five. Domestic skills -- Chapter Six. Recreation/leisure skills -- Chapter Seven. Vocational skills -- Chapter Eight. Motor skills -- Chapter Nine. Communication skills -- Chapter Ten. Functional academic skill -- Chapter Eleven. Integration issues and strategies.
Includes bibliographical references and index.
Keywords: CHILDREN WITH DISABILITIES